EMOSIONAL SKILL CABANG OLAHRAGA PENCAK SILAT MERPATI PUTIH - Syifa, Nisa Nur; Muhtar, Tatang; Alif, Muhammad Nur (Fakultas Ilmu Keolahragaan Unimed, 2024)
Emotional Skill is an emotional disorder or emotional regulation disorder, referring to a condition where a person has difficulty in regulating and managing their emotions effectively, this involves difficulty in regulating and managing their emotions effectively, In demonstrating martial arts movements, a person must be able to pay attention and stabilize their emotions when doing movements or when competing. This research aims to find out that there is an emotional analysis of the white pigeon pencak silat sport. The research method used in this study uses juantitative methods and descriptive design aims to describe or describe a certain phenomenon or characteristic that exists in the population or sample being studied. This design focuses on collecting data systematically and in detail about the observed variables, without manipulating or controlling variables. This research uses an intrumant in the form of an emotional skill questionnaire that is distributed to the sempel to obtain the data needed in this research. Sempel in this study there were 25 pencak silat athletes with white pigeons in Cimahi city. With Stratified random sampling technique. The result of the t test with a significant value (2 tailed) obtained is (0.000). Then the significant value (2 tailed) 0.000 < 0.05 so that Ha is accepted. Based on the data processing, researchers can conclude that the results of their research have an influence from the Emotional Skil Sports Branch Pencak Silat Merpati Putih